Assessment of Executive Functions in Preschool Children With Sickle Cell Anemia. (30th May 2018) - Downes, Michelle; Kirkham, Fenella J.; Telfer, Paul T.; de Haan, Michelle
Abstract: Objectives: Children with sickle cell anemia (SCA) are commonly reported to experience executive dysfunction. However, the development of executive function (EF) in preschool-age children without stroke in this patient population has not been investigated so it is unclear when and how these deficits emerge.Methods: This case-control study examines the feasibility of assessing the early development of executive functioning in 22 preschool children years with SCA in the domains of processing speed, working memory, attention, inhibitory control, and cognitive flexibility, as well as everyday function, in comparison to matched control children.Results: A pattern of potential deficits in early emerging executive skills was observed in the domains of inhibitory control and cognitive flexibility. Parents reported no differences for everyday EF and no significant differences were observed for working memory and processing speed.Conclusions: Results suggest that deficits in everyday executive difficulties, working memory, and processing speed, as commonly reported for older children with SCA, may not yet have emerged at this early developmental stage, despite specific deficits in cognitive flexibility and inhibitory control on behavioral measures. The feasibility of using available executive measures with preschool age children to characterize the development of early EF skills is discussed. ( JINS, 2018, 24, 949–954)